PENGARUH WORK FROM HOME TERHADAP PRODUKTIVITAS DOSEN POLITEKNIK NEGERI AMBON - RICARDO MANARINTAR SIMARMATA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This paper aims to examine the impact work from home (WFH) on the lecturer productivity of Politeknik Negeri Ambon. This research is need to be discussed because the increase of the productivity can be influenced by work from home. The population in this study were all lecturer at Politeknik Negeri Ambon with a total of 37 lecturers. The research design used is quantitative research with a descriptive approach with an emphasis on theory testing through measurement of research variables through the distribution of research questionnaires. The sampling technique used is nonprobability sampling with the technique taken is census. The analysis technique is to use linear regression with SPSS 21.0 software. Limitations: constraints of respondents who were asked for data virtually and limited scope of the research. Result: The results of this study show that work from home variable have a significant positive effect on the lecturer productivity partially.